Audience Participation in Theatre - White, G. author. aut Link
X, 224 p.
Keywords: This book asks that we consider the practices that facilitate audience participation on equal terms with other elements of the theatre maker's art; it offers a theoretical basis for this new approach, illustrated by examples from diverse participatory performances.